Spatializationof service coverage of sanitation basic and of human development index of municipalities the Marajó, Pará - Crispim, Diêgo Lima; Rodrigues, Rodrigo Silvano Silva; Vieira, Artur Sales de Abreu; Silveira, Rafaela Nazareth Pinheiro de Oliveira; Fernandes, Lindemberg Lima (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2016)
The Access to basic sanitation services has caused concern, particularly in the states of North and Northeast regions, and more specifically in municipalities with limited budget, of small size and distant from the capital, where they are located populations in vulnerable social situations. In this context, the aim of this research was to analyze the situation of some services of environmental sanitation and the index of development human municipal of municipalities the mesoregion of Marajó, state of Pará. For that was lifted up some information through secondary data of the municipalities that make up the region under study, with an emphasis on some sanitation and IDHM services. The results showed that the coverage rate of the sewage collection serviceleaves extremely to be desired, particularly regarding the collection and treatment of sewage. How much the destination of solid waste, it was found that some municipalities adopt an inappropriate manner, depositing them in open dumps. The availability of information in the databases of agencies and entities is critical to assist in determining priorities in the actions of government and civil society in relation to sanitation services.